The lncRNA ANRIL Gene rs2151280 GG Genotype is Associated with Increased Susceptibility to Recurrent Miscarriage in a Southern Chinese Population - Che D (Dove Medical Press, 2021)
Di Che,1,* Zhenzhen Fang,2,* Hanran Mai,1,* Yufen Xu,1 LanYan Fu,1 Huazhong Zhou,1 Linyuan Zhang,1 Lei Pi,1 Xiaoqiong Gu1 1Department of Clinical Biological Resource Bank, Guangzhou Institute of Pediatrics, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Program of Molecular Medicine, Guangzhou Women and Children’s Hospital, Zhongshan School of Medicine, Sun Yat-sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoqiong GuDepartment of Clinical Biological Resource Bank, Guangzhou Institute of Pediatrics, Guangzhou Women and Children’s Medical Center, Guangzhou Medical University, 9 Jinsui Road, Guangzhou, 510623, Guangdong, People’s Republic of ChinaTel/Fax +86-20-38076561Email guxiaoqiong@gwcmc.orgBackground: Genetic factors may play an important role in susceptibility to recurrent miscarriage. Some cardiovascular disease-related candidate genes have been shown to be associated with recurrent miscarriage. Long noncoding RNA ANRIL has been confirmed to be associated with susceptibility to various diseases, such as cardiovascular disease. However, it remains unclear whether the ANRIL gene polymorphism is related to recurrent miscarriage susceptibility.Methods: Three ANRIL gene polymorphisms (rs2151280, rs1063192 and rs564398) were genotyped in 819 controls and 610 recurrent miscarriage patients through TaqMan real-time polymerase chain reaction. The odds ratios and 95% confidence intervals (CIs) were used to assess the strength of each association.Results: Our results showed that the ANRIL rs2151280 GG genotype was associated with increased susceptibility to recurrent miscarriage (GG vs AA: adjusted OR=1.527, 95% CI=1.051– 2.218, p=0.0262; GG vs AG/AA adjusted OR=1.460, 95% CI=1.021– 2.089, p=0.0381). By combining the analysis of the risk genotypes in the three SNPs, we found that individuals with 2– 3 risk genotypes had a significantly increased risk of recurrent miscarriage compared with those with a 0– 1 risk genotype (adjusted OR=1.728, 95% CI=1.112– 2.683, p=0.0149). This risk was more significant in subgroups of women less than 35– 40 years of age and women with 2– 3 miscarriages.Conclusion: These results suggested that a specific SNP in the ANRIL gene may be associated with increased susceptibility to recurrent miscarriage in a southern Chinese population.Keywords: recurrent miscarriage, lncRNA ANRIL, genetic susceptibility, polymorphism